Substance and behavioral addictions may share a similar underlying process of dysregulation. (21st April 2017) - Sussman, Steve; Rozgonjuk, Dmitri; van den Eijnden, Regina J. J. M.
Abstract : Commentary to:How can we conceptualize behavioural addiction without pathologizing common behaviours?